Differentiating RNA from DNA by a molecular fluorescent probe based on the "door-bolt" mechanism biomaterials. (September 2018) - Yao, Qichao; Li, Haidong; Xian, Liman; Xu, Feng; Xia, Jing; Fan, Jiangli; Du, Jianjun; Wang, Jingyun; Peng, Xiaojun
Abstract: Although excellent florescent probes have been developed for DNA, good probes for RNA remain lacking. The shortage of reported and commercial RNA probes is attributable to their severe interference from DNA. As DNA and RNA have similar structures but different functions, it has been an imperative challenge to develop RNA probes that differentiate from DNA. In this study, an NIR fluorescent probe, NBE, is described, which contains a bulky julolidine group that can fit in a spacious RNA pocket and emit intense fluorescence. However, NBE has no response to DNA, as it cannot intercalate into the double strands or even in the DNA minor groove. The sensing mechanism is similar to the effect of a door-bolt. NBE shows excellent performance in RNA sensing (outstanding photostability, high selectivity and fast response), whether in aqueous buffers, fixed cells or living cells. These findings might provide not only a potential imaging tool but also a new design strategy for the recognition of RNA while avoiding interference from DNA. Graphical abstract: Image 1